Glycoproteoform Profiles of Individual Patients’ Plasma Alpha-1-Antichymotrypsin are Unique and Extensively Remodeled Following a Septic Episode - Čaval, Tomislav; Lin, Yu-Hsien; Varkila, Meri; Reiding, Karli R.; Bonten, Marc J. M.; Cremer, Olaf L.; Franc, Vojtech; Heck, Albert J. R. (Frontiers in Immunology, 2021)
Sepsis and septic shock remain the leading causes of death in intensive care units (ICUs), yet the pathogenesis originating from the inflammatory response during sepsis remains ambiguous. Acute-phase proteins are typically highly glycosylated, and the nature of the glycans have been linked to the incidence and severity of such inflammatory responses. To further build upon these findings we here monitored, in molecular detail, the longitudinal changes in the glycoproteoform profiles of alpha-1-antichymotrypsin (AACT) extracted from plasma of individual septic patients. For each patient we included four different time-points, including post-operative (before sepsis) and following discharge from the ICU. We used high-resolution native mass spectrometry to qualitatively and quantitatively monitor the multifaceted glycan microheterogeneity of AACT, which allowed us to monitor how changes in the glycoproteoform profiles reflected the patient's physiological state. Although we observed a general trend in the remodeling of the AACT glycoproteoform profiles, e.g. increased fucosylation and branching/LacNAc elongation, each patient exhibited unique features and responses, providing a resilient proof-of-concept for the importance of personalized longitudinal glycoproteoform profiling. Importantly, we observed that the AACT glycoproteoform changes induced by sepsis did not readily subside after discharge from ICU.